(untitled) (Analysis in Theory and Applications, 2022)
In this article, we obtain some weighted estimates for Marcinkiewicz integrals with non-smooth kernels on spaces of homogeneous type. The weight ω considered here belongs to the Muckenhoupt’s class A_∞. Moreover, weighted estimates for commutators of BMO functions and Marcinkiewicz integrals are also given.